A City: Elazığ, A Sector: Viticulture, A Product: Öküzgözü Grape, A Brand: Elazığ Wine - Yücel, Nurcan (Fırat University, 2015)
Viticulture and grape products industries with 130,000 tons of annual production capacity, in terms of financial income and the tendency have a very important place in our country’s economy and agriculture sector. Especially identified with the province of Elazig, brand name products, unique to the area's micro-climate traditionally grown Öküzgözü and Boğazkere grapes must be evaluated in terms of branding and marketing. At this point, a globally recognized brand Öküzgözü and Boğazkere grapes as the desired product in terms of quality has led to many advances in agriculture in Elazığ. Especially the establishment of a monopoly winery in the 1930s, the grape product branding and traditional viticulture has led to a change in the way. In this study, the importance of Elazig grapes in the world, Elazig viticulture industry sector problems, branding and marketing problems of grapes will be examined. İndustry analysis work with the managers of Grape producers' association, viticulture clustering in the region and marketization were examined the cluster analysis

Ülkemiz ekonomisi ve tarım üretimi açısından Bağcılık sektörü ve üzüm ürünleri yıllık 130.000 tonluk üretim rakamı ile, maddi gelir ve istihdam kapasitesi açısından çok önemli bir yere sahiptir. Özellikle Elazığ ili ile özdeşleşen, bölgenin mikro klima iklimine has geleneksel olarak yetiştirilen Öküzgözü ve Boğazkere üzümlerinin markalaşma ve pazarlama karması açısından değerlendirilmesi gerekmektedir. Bu noktada; Elazığ’ın markalarından Öküzgözü ve Boğazkere üzümlerinin dünya şaraplık üzüm çeşidi ve kalitesi açısından aranan ürün olması, bölgede bağcılık tarımının çok gelişmesini sağlamıştır. Özellikle 1930’lu yıllarda Tekel Şarap Fabrikasının kurulması, üzüm ürününün markalaşmasına ve geleneksel bağcılığın şekil değiştirmesine öncülük etmiştir. Bu çalışmada, Elazığ’ın marka olma yolunda olan Bağcılığın sektör ve pazarlama problemleri, Dünyada Elazığ üzümlerinin önemi, markalaşma problemleri ile ürünün markalaşamamasından dolayı ortaya çıkan problemler incelenecektir. Ayrıca, Üzüm Üreticileri Birliği yöneticileriyle sektör analizi, bölgede bağcılık kümelenmesi ve piyasalaşması konuları kümelenme analizi şeklinde ele alınacaktır.
BİR ŞEHİR: ELAZIĞ, BİR SEKTÖR: BAĞCILIK, BİR ÜRÜN: ÖKÜZGÖZÜ ÜZÜMÜ, BİR MARKA: ELAZIĞ ŞARABI